Analisis Proses Produksi Program TVRI Sport Pagi - Adetya Perdanaraya Putra Wiedyudja; Harmonis Harmonis (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Television is a mass media that is inseparable in human life. Television shows other people's lives and gives ideas about carrying out activities. TVRI Sport Pagi is a program that broadcasts information about the world of sports both domestically and internationally. The problem in the research is how the production process for the TVRI Sport Pagi news program is carried out. This research aims to determine the flow of the TVRI Sport Pagi news program production process from pre-production, production, post-production as well as to find out the inhibiting and supporting factors in the TVRI Sport Pagi news program process. The research method used is descriptive qualitative with documentation and interview data collection techniques. From the research that has been carried out, it can be concluded that the production process for the TVRI Sport Pagi news program goes through several processes so that it can be watched by the audience in accordance with Standard Operational Procedures. So that it can produce a quality TVRI Sport Pagi news program even though it has a number of obstacles or supporting and inhibiting factors in the production process.